Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.3171/jns.1997.86.1.0013
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma: is the 5-year survival rate improving?

Abstract: A series of 80 cases of medulloblastomas in children undergoing operation and postoperatively followed between 1980 and 1990 at Great Ormond Street Hospital for Children (GOSH) has been reviewed and compared to an earlier series reported from the same institution by McIntosh. The overall 5-year survival rate for the present series was 50%, although three patients died after surviving 5 years. The operative mortality rate was 5%. Survival analysis revealed that the presence or absence of spinal metastases and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 55 publications
5
58
0
5
Order By: Relevance
“…1,7,30,31 Among these patients, 2 had early relapse in the spinal axis despite more aggressive therapy. In agreement with other reports on adults 1,4,19,32,36,40 and children, 17,37,48 we found that the presence of metastatic disease at presentation was an important prognostic factor for overall and event-free survival times. In a larger multicenter series, 7 metastatic disease did not appear to be correlated with a worse prognosis, but data were available for only 61% of the patients, and half of the patients with Stage M0 medulloblastomas received chemotherapy either before or after, or both before and after, radiotherapy.…”
Section: Prognostic Factorssupporting
confidence: 82%
“…1,7,30,31 Among these patients, 2 had early relapse in the spinal axis despite more aggressive therapy. In agreement with other reports on adults 1,4,19,32,36,40 and children, 17,37,48 we found that the presence of metastatic disease at presentation was an important prognostic factor for overall and event-free survival times. In a larger multicenter series, 7 metastatic disease did not appear to be correlated with a worse prognosis, but data were available for only 61% of the patients, and half of the patients with Stage M0 medulloblastomas received chemotherapy either before or after, or both before and after, radiotherapy.…”
Section: Prognostic Factorssupporting
confidence: 82%
“…They are known to exhibit predominantly neuronal differentiation and a tendency to metastasize via cerebrospinal fluid pathways. Although significant advances have been made in the treatment of MBs, the 5-year survival rate of 50% still represents an unfavorable course (1). Because the initial step of intraspinal spread is characterized by both seeding of tumor cells on the arachnoid or pia mater as well as the lysis of collagenous barriers to enhance angiogenesis and local invasion, attention has been focused on the ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent improvements in the survival of patients with MB, secondary tumor growth is observed in up to 40% of patients, resulting in a poor prognosis. Dissemination to the leptomeninges of the brain or seeding of tumor cells in the neuroaxis are the most common forms of metastasis (1)(2)(3)(4)(5). The underlying molecular mechanisms of brain tumor invasiveness are complex and have been studied mainly in malignant glial tumors and are closely related to proteolytic degradation of the extracellular matrix (ECM; Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although advances in multimodality therapy with aggressive surgery, radiation and chemotherapy have led to dramatic improvement in the prognosis over the past decades, the 5-year survival rate still ranges from 50 to 70%. [2][3][4] In particular, leptomeningeal dissemination that results from metastases through the CSF space is thought to be one of the most hideous features of medulloblastomas and characterizes their malignant behavior. The CSF metastases appear as foci of nodular or diffuse contrast enhancement in the leptomeninges or on the ventricular surface in one-third of the patients at presentation.…”
Section: Introductionmentioning
confidence: 99%